Analysis of Acehnese People's Preferences for Sharia Banks After the Merger of 3 Sharia Commercial Banks - Nasri Zarman; Eliana; Ferdi Nazirun Sijabat (STMIK Indonesia Banda Aceh, 2025)
Since the enactment of Aceh Qanun Number 11 of 2018 concerning Sharia Financial Institutions, it has required banks in Aceh to merge and convert into sharia banks which has had an impact on the people of Aceh. This incident is in the world's spotlight because the government's performance in its seriousness in developing the Islamic economy, especially sharia banking, needs to be appreciated after its success in combining three Sharia Commercial Banks to occupy the 7th position with the largest assets nationally, which was initially in 20th or 30th position and currently, Indonesia is able to generate assets of IDR 240 trillion or the equivalent of USD 16.78 billion, so it is included in the ranks of the 10 largest sharia banks in the world. This research aims to analyze the partial and simultaneous influence on the Acehnese people's preferences for Sharia Banks after the merger of three Sharia Commercial Banks. This research method is a quantitative method, with the number of samples in this research being 100 respondents. Research data was collected through questionnaires distributed to respondents. This research data was analyzed using a multiple linear regression model and processed using SPSS (Statistical Package For The Social Sciences). The results of this research show that literacy, inclusion, reputation, religiosity partially and simultaneously influence the Acehnese people's preferences for Sharia Banks after the Merger of three Sharia Commercial Banks.